Reference values for handgrip strength, five times sit-to-stand and gait speed in patients on hemodialysis - Duarte, Marvery P.; Nobrega, Otavio T.; Vogt, Barbara P.; Pereira, Marina S.; Silva, Maryanne Z. C. [UNESP]; Mondini, Dario R.; Disessa, Henrique S. [UNESP]; Adamoli, Angelica N.; Buendchen, Daiana C.; Sant'Helena, Bruna R. M.; Krug, Rodrigo R.; Bohlke, Maristela; et al. (Oxford Univ Press, 2024)
Background. Low levels of muscle strength and physical performance predict adverse clinical outcomes in patients on hemodialysis; however, reference values remain lacking. We described reference values for handgrip strength, five times sit-to-stand (STS-5) and 4-m gait speed in a large-scale sample of patients on hemodialysis. Methods. Baseline data from the SARCopenia trajectories and associations with adverse clinical outcomes in patients on HemoDialysis (SARC-HD) study were analyzed. Muscle strength was evaluated using handgrip strength and the STS-5, whereas physical performance was evaluated using usual 4-m gait speed before a midweek dialysis session. Sex- and age-specific smoothed reference curves for each test at the 3rd, 15th, 50th, 85th and 97th percentiles were constructed using generalized additive models for location shape and scale. Comparisons between sex and age were also performed. Results. Data from 1004 patients (39% female; 19-96 years; 49% >= 60 years) were analyzed. Declines in muscle strength and physical performance were observed with advancing age in both sexes. However, among males, muscle strength and performance were similar between 18 and 49 years of age. Males exhibited substantially greater performance in handgrip strength [10.3 kg, 95% confidence interval (CI) 9.1 to 11.4] and 4-m gait speed (0.10 s, 95% CI 0.05 to 0.14) compared with females. Older patients, independent of sex, exhibited poorer performance on most tests. Lower handgrip strength in the arm with arteriovenous fistula was observed in both sexes (males -2.3 kg, 95% CI -2.8 to -1.7; and females -2.1 kg, 95% CI -2.6 to -1.6). Conclusion. Reference values obtained in this study may be used in clinical and research settings to identify patients on hemodialysis with low physical function according to sex and age. Future studies should test these reference values as potential predictors of adverse clinical outcomes.
Keywords: chronic kidney disease; muscle strength; physical performance; reference values; sarcopenia